2011
DOI: 10.1021/om200586d
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Description of Triplet Silylenes Evolved from H2Si═Si

Abstract: The concept of finding triplet ground state silylenes has been the subject of many experimental and theoretical studies. 1 Why? The answer is in the low ability of heavier group 14 elements to form hybrid orbitals. They prefer the (ns) 2 (np) 2 valence electron configuration, which leads to the divalent singlet ground state H 2 M (M = Si, Ge, Sn, Pb). 2 While methylene (H 2 C) has a triplet ground state with a singletÀtriplet energy separation (ΔE S-T = E T À E S ) of À9.0 kcal/ mol, 3 the ground state of sily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
4
12
0
Order By: Relevance
“…In 2011, Momeni et al studied on triplet silavinylidene (>C═Si:) and confirmed their latter choice for the silylidene structures. They indicated that silavinylidene preferred to form π 1 p 1 triplet state over n 1 p 1 , due to the high energy gap between the 3s and 3p orbitals of Si . So, due to the high similarity between silylene and gemylene, we guess that germavinylidene behave in the same manner as well as silylene and our results confirm this.…”
Section: Results and Disscusionsupporting
confidence: 90%
See 1 more Smart Citation
“…In 2011, Momeni et al studied on triplet silavinylidene (>C═Si:) and confirmed their latter choice for the silylidene structures. They indicated that silavinylidene preferred to form π 1 p 1 triplet state over n 1 p 1 , due to the high energy gap between the 3s and 3p orbitals of Si . So, due to the high similarity between silylene and gemylene, we guess that germavinylidene behave in the same manner as well as silylene and our results confirm this.…”
Section: Results and Disscusionsupporting
confidence: 90%
“…Interestingly, a total of twelve triplet germavinylidenes are encountered as global minimum with rather high stabilities. In accordance to Worthington and Cramer statements and in contrast to Momeni findings on the stabilization of vinylidene silylenes, our results indicate that in the case of germavinylidene, the stabilizing P Ge → σ* N─C interaction is detectable in our triplets (Table ). So, we confirm that σ‐electron withdrawing interactions bring effects on the germylene p orbital stabilization, preferentially.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…B.01) [32] at 298.15 K and 1 atm, and converged structures (starting geometries were obtained from the Supporting Information in ref. [19]) were absent imaginary frequencies.…”
mentioning
confidence: 93%
“…In recent work, the singlet-triplet excitation energies (E S-T ) for a suite of mono-and disubstituted R 1 R 2 Si=Si silylene derivatives (where R 1 /R 2 =H, CH 3 , NH 2 , OH, and F), as well as H 2 C=Si and HN=Si, were calculated at the CCSD(T)/6-311++G(d,p)//QCISD/6-31G(d) and B3LYP/AUG-cc-pVTZ//B3LYP/6-31+G(d) levels of theory [19] (Table 1). However, density functional theory (DFT) methods, particularly using the B3LYP functional, are known to significantly underestimate the E S-T of organic compounds (see, ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation